Kebijakan Pemberdayaan Perempuan Di Bidang Ekonomi Dalam Upaya Mewujudkan Pembangunan Berkelanjutan Ramah Gender: Studi Kasus : Perbandingan Kebijakan permerdayaan perempuan Kota Surabaya dan Probolinggo dibidang UMKM - Elitttaria Ginting; Hagawaomasi Zokho Sihura (Jurnal Inada: Kajian Perempuan Indonesia di Daerah Tertinggal, Terdepan, dan Terluar, 2022)
The position of women will improve only when women can be independent and able to control the decisions related to their lives. Empowering women has many positive impacts on the development of the country. Therefore, it is necessary from now on to invest in girls or young women. Investments in women can expand women's access to education and various employment opportunities. When girls and young women have better access to education, they can have better careers. The increased participation of women in the labor market can boost the economic growth of their countries. The leadership of women in various regions has given different colors. Innovation for local governments is a necessity that is pursued for the prosperity and welfare of the community, this is related to innovation based on the Mayor of Surabaya, Ir. Tri Rismaharini, MT, and Hj Puput Tantriana Sari who is well known for innovation and creative ideas to build the city of Surabaya. This lesson attempts to analyze the role of female leaders, leadership effectiveness, various forms of leadership, processes, key success factors, leadership barriers in building leadership innovation for the mayor of Surabaya.